THE RUSSIAN LANGUAGE IN THE MODERN WORLD: TRENDS AND CHALLENGES (American Journal of Pedagogical and Educational Research, 2024)
The Russian language holds immense historical, cultural, and geopolitical significance. This scientific article examines the role of the Russian language in the modern world, exploring its global reach, evolving status, and the challenges it faces. Drawing on linguistic, sociocultural, and technological perspectives, this study provides a comprehensive analysis of the current state of the Russian language and its implications for language policy, education, and intercultural communication. The article also discusses the impact of globalization, digital technologies, and diaspora communities on the Russian language landscape. By understanding these dynamics, stakeholders can make informed decisions to promote the vitality and relevance of the Russian language in a rapidly changing world.